A critical appraisal of Friends of the Irish Environment v Government of Ireland. Issue 1 (16th October 2020) - Kelleher, Orla
Abstract: This case note examines the judgement of the Irish Supreme Court quashing Ireland's National Mitigation Plan and the earlier judgement of the High Court dismissing judicial review proceedings in Friends of the Irish Environment v Government of Ireland . It explores the contrasting legal reasoning of the two courts on the issues of standard of review, justiciability, compliance of the National Mitigation Plan with the Climate Action and Low Carbon Development Act 2015, locus standi and the constitutionality and compatibility of the National Mitigation Plan with the European Convention on Human Rights.